A sentence completion procedure as an alternative to the Autobiographical Memory Test for assessing overgeneral memory in non-clinical populations. - Raes, F; Hermans, D; Williams, J; Eelen, P (2007)
Overgeneral memory (OGM) has been proposed as a vulnerability factor for depression (Williams et al., 2007) or depressive reactivity to stressful life-events (e.g., Gibbs and Rude, 2004). Traditionally, a cue word procedure known as the Autobiographical Memory Test (AMT; Williams and Broadbent, 1986) is used to assess OGM. Although frequently and validly used in clinical populations, there is evidence suggesting that the AMT is insufficiently sensitive to measure OGM in non-clinical groups. Study 1 evaluated the usefulness of a sentence completion method to assess OGM in non-clinical groups, as an alternative to the AMT. Participants were 197 students who completed the AMT, the Sentence Completion for Events from the Past Test (SCEPT), a depression measure, and visual analogue scales assessing ruminative thinking. Results showed that the mean proportion of overgeneral responses was markedly higher for the SCEPT than for the standard AMT. Also, overgeneral responding on the SCEPT was positively associated to depression scores and depressive rumination scores, whereas overgeneral responding on the AMT was not. Results suggest that the SCEPT, relative to the AMT, is a more sensitive instrument to measure OGM, at least in non-clinical populations. Study 2 further showed that this enhanced sensitivity is most likely due to the omission of the instruction to be specific rather than to the SCEPT's sentence completion format (as opposed to free recall to cue words).